Our experiences on the reconstruction of lateral scalp burn alopecia with tissue expanders. Issue 3 (May 2015) - Guzey, Serbulent; Alhan, Doğan; Şahin, Ismail; Aykan, Andaç; Eski, Muhitdin; Nişancı, Mustafa
Highlights Restoration of lateral scalp alopecia. Newly designed algorithm was created. Good and standardized cosmetic results can be obtained by this approach.